Tingkat Kualitas Audit Perusahaan Keluarga Terhadap Tenur dan Rotasi Audit - Ananto Prabowo; Desy Ria Wibawa (LPPM ISNJ Bengkalis, 2021)
The purpose of the research is to determine the influence of audit tenure and rotation on audit quality at the family businesses listed in the Indonesian Stock Exchange from 2009 to 2017, with the financial sector as the exemption. The reason for research is that the quality of the financial report is essential for decision-making purposes both internally and externally. This research is quantitative by utilizing secondary data. The analysis uses multiple regressions. The research showed that public accountants’ tenure and rotation have a positive impact but not significant on audit quality, where tenure and rotation on accounting firms have a negative impact but do not significantly influence audit quality.